Impact of alkaloids extract of Moringa olievera Lam. leaves on the development, fertility and demography of the southern cowpea beetle insect Callosobruchus maculatus (F.) (Coleoptera: Bruchidae) - Tahani Nouri Jassim; Soolaf A Kathiar; Hazim Idan Al Shammari (مجلة بغداد للعلوم)
The Southern Cowpea Beetle Callosobruchus maculatus (F.) is one of the most widespread insect pests of stored legumes, causing a considerable loss during storage, decreasing the net weight of the crops, and resulting in reduced the quality of the crops. This study has been conducted to determine the lifetime, fertility and life table parameters of C. maculatus by using an alkaloids extract from Moringa oleifera leaves at different concentrations 1000, 2000, and 3000 ppm. The result was shown that the lowest survival rate was 49% at a concentration of 1000, 2000 ppm, as compared with the control which was 77%. The lowest reproductive rate (Ro) was 4.76 female/female/generation at the concentration of 1000 ppm, compared with the control which was 10.34 female/ female /generation while the lowest rate of egg hatching was 62% at the concentration of 3000 ppm as compared with the control 88%. Similarly, the sex ratio of male: to female was decreased after the use of the three concentrations, mostly at the concentration of 1000 ppm, in which the ratio was 1.31:0.69 compared to 1.11:0.89 for the control. Overall, the life tables curve shows that the survival rate, the ratio of the females and the productivity was affected in a negative way causing a decline in the whole insect population. It is clear from the above that the alkaloids extract of the leaves of the Moringa plant is effective and has an impact on the insect population, and can be an eco-friendly method of controlling on pest population.